1998
DOI: 10.1111/j.1744-6570.1998.tb00256.x
|View full text |Cite
|
Sign up to set email alerts
|

Influences of the Virtual Office on Aspects of Work and Work/Life Balance

Abstract: Millions of employees now use portable electronic tools to d o theirjobs from a "virtual office" with extensive flexibility in the timing and location of work. However, little scholarly research exists about the effects of this burgeoning work form. This study of IBM employees explored influences of the virtual office on aspects of work and worwlife balance as reported by virtual office teleworkers (n = 157) and a n equivalent group of traditional office workers (n = 89). Qualitative analyses revealed the perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
262
1
9

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 362 publications
(299 citation statements)
references
References 4 publications
7
262
1
9
Order By: Relevance
“…It is also found that productivity can be increased as a result of eliminating the wasted time that a real commute requires (Davis, 1995;Hill et al, 1998). The telecommuting programme can be used to reduce traffic jams and improve air quality (Siha et al, 2006).…”
Section: The Advantages Of Telecommuting Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also found that productivity can be increased as a result of eliminating the wasted time that a real commute requires (Davis, 1995;Hill et al, 1998). The telecommuting programme can be used to reduce traffic jams and improve air quality (Siha et al, 2006).…”
Section: The Advantages Of Telecommuting Implementationmentioning
confidence: 99%
“…Training must be supported by top management and should be provided for both telecommuters and their managers (Potter, 2003). Results of a study by Hill et al (1998) on the virtual workplace of IBM employees showed that having good training is essential for both managers and telecommuters (Kellyman & Jennifer, 2005).…”
Section: The Driving Factors For Telecommuting Adoptionmentioning
confidence: 99%
“…Together, these factors, related to the location of work, the timing of work, and the quality of work life, can increase productivity. Subsequently, telecommuting improved productivity on the jobs (Fister 1999;Ervin 1998;Fortier 1998;Hill et al 1998;White Paper 1997;Shellenbarger 1997;Sullivan 1992;and Janal 1991) and the improvement is ranged between 20 to 70 percent (Ervin 1998;Khairallah 2001;Straton 2001;and Verespej 2001). This also supported by Hawkins et al (1997), CNN (1996), Langhoff (1996), and Pacholczyk et al (1995) as they stated that telecommuting improved productivity and their organizations benefited from the practice.…”
Section: Telecommuting Factorsmentioning
confidence: 99%
“…Telecommuting had been promoted extensively in the United States somewhere in the 70s as personal computer, and portable modem had been made available (Roseberry 2001;USDT 1993;Hill et al 1998). Telecommuting, as defined by Williams et al (1999) is a way of working at home with telecommunications -phone, fax, and computer-between office and home.…”
Section: Equipmentsmentioning
confidence: 99%
See 1 more Smart Citation